Traditional and molecular methods for diagnosing bacterial meningitis in Erbil city, Iraq (Baghdad Science Journal, 2024)
Bacterial meningitis is a leading cause of illness and death worldwide. It is crucial for clinical and public health care, as well as disease control, to identify the meningitis-causing agent promptly. Between June 2021-February 2022, a total of 100 cerebrospinal fluid (CSF) and blood samples were collected from suspected cases of meningitis admitted to Raparin Paediatric Teaching Hospital, Erbil city-Iraq. Cytochemical, cultural, and biochemical tests were conducted, and confirmed by molecular techniques. Bacterial culture findings were positive in 7% of CSF samples and just one positive among blood samples. The most common pathogens found by cultural characteristics and VITEK 2 Compact System were Staphylococcus sciuri in two cases 2%, Staphylococcus xylosus in one case 1%, Escherichia coli in two instances 2%, Enterococcus casseliflavus and Micrococcus luteus each in one case 1%. Staphylococcus sciuri, Staphylococcus xylosus, Enterococcus casseliflavus and Micrococcus luteus were first recorded as bacterial meningitis in Erbil/Iraq. All isolates were confirmed by PCR assay. All clinical isolates were screened for some antimicrobial sensitivity, meropenem and tobramycin have been shown to be totally resistant 100% to all isolated bacteria, furthermore, isolated E coli showed highly resistant 100 to cefotaxime, gentamycin, pencillin, ceftriaxone, rifampin, amoxicillin/clavulanic acid, ceftazidime, erythromycin, ampicillin, and clindamycin, while they were sensitive (100%) to amikacin and imipenem as well as all the gram positive bacteria were resistant 100% to optochin and sensitive (100%) to gentamycin, and trimethoprim. In bacterial meningitis patients, high C-reactive protein (CRP) >6 mg/dl, high CSF protein >50 mg/dl, low CSF glucose level <40 mg/dl and high leukocyte count >100 cells/mm3 were all substantially diagnostic.